Penerapan Problem Based Learning Berbantuan Media Augmented Reality untuk Meningkatkan Hasil dan Kemandirian Belajar - Ekayogi, I Wayan (Jurnal Didaktika Pendidikan Dasar, 2023)
This research aims to improve learning outcomes and student learning independence by applying a problem-based learning model assisted by augmented reality media in III grade students at SD Negeri 5 Sebatu. This research is a classroom research action conducted in two cycles. The research subjects were III grade students, the total number of the students were 24 students. The object of the research is a problem-based learning model assisted by augmented reality media, learning outcomes and learning independence. The data in the research were collected by test and observation methods. Data were analyzed using descriptive statistical and quantitative descriptive analysis methods. Based on the results of data analysis, the average percentage of students cognitive learning outcomes in cycle I was 67.08% (moderate category), increasing to 81.25% (high category) in cycle II. The results of observations of learning independence cycle I meeting 1were in the "low" category and meeting 2 was in the "moderate" category. Whereas in cycle II meeting 1 and meeting 2 were categorized as "high". Based on the results of the research, it can be concluded that the application of the problem-based learning model assisted by augmented reality media can improve learning outcomes and learning independence of the III grade students.